Potential interactions between HIV drugs, ritonavir and efavirenz and anticancer drug, nilotinib—a study in primary cultures of human hepatocytes that is applicable to HIV patients with cancer. (27th May 2014) - Pillai, Venkateswaran C.; Parise, Robert A.; Christner, Susan M.; Rudek, Michelle A.; Beumer, Jan H.; Venkataramanan, Raman
Abstract Nilotinib is used to treat chronic myeloid leukemia (CML), and is metabolized by CYP3A. With a black‐box warning for QT prolongation, which is exposure dependent, controlling for drug interactions is clinically relevant. Treatments of HIV patients with CML are with HAART drugs, ritonavir and efavirenz, may cause complex drug interactions through CYP3A inhibition or induction. We evaluated the interactions of ritonavir or efavirenz on nilotinib using human hepatocytes and compared these interactions with those of ketoconazole or rifampin, classical CYP3A inhibitor and inducer, respectively. Hepatocytes were treated with vehicle, ritonavir (10 μM), ketoconazole (10 μM), efavirenz (10 μM), or rifampin (10 μM) for 5 days. On day 5, nilotinib (3 μM) was coincubated for an additional 24–48 hours. The concentrations of nilotinib were quantitated in collected samples (combined lysate and medium) by LC‐MS. Apparent intrinsic clearance (CLint, app) of nilotinib was lowered 5.8‐ and 3.1‐fold, respectively, by ritonavir and ketoconazole. Efavirenz and rifampin increased the CLint, app of nilotinib by 2.1‐ and 4.1‐fold, respectively. The clinically recommended dose (300 mg twice daily) of nilotinib may have to be reduced substantially (150 mg once daily) or increased (400 mg thrice daily), respectively, to achieve desired drug exposure, when ritonavir or efavirenz is co‐administered.